Maori times, Maori places : prophetic histories - Sinclair, Karen, 1947- (Rowman & Littlefield, 2003)
This book is a compilation of twenty-five years of fieldwork with a group of Maori. It is an examination of oral histories, notebooks of songs, diaries, accounts of pilgrimages, and life histories. Critical issues are addressed including written and unwritten histories, colonialism, gender, and membership in Maramatanga. This book examines in great detail what scholars of New Zealand have grown to understand, there is no monolithic Maori voice.